The Impact of Macroeconomic, Oil Prices and Socio-Economic Factors on Exchange Rate in Pakistan: An ARDL Approach - Ramakrishnan, Suresh; Butt, Shamaila; Anuar, Melati Ahmad (International Journal of Economics and Financial Issues, 2017)
The study examines the linkages among the nominal exchange rate, oil prices, terrorism and three selected macroeconomic variables: real growth rate, inflation rate and interest rate. The paper employed Auto Regressive Distributed Lag to test the long run and short run dynamics over the period 1980 to 2015 in the context of Pakistan. A novel technique to this research is that we demarcate the relationship among macroeconomic variables, financial variable and socio-economic variable. The findings of the research depict a robust long run relationship among variables. Furthermore, the results showed that the adjustment process is slow and short run adjustment indicating that the discrepancies adjust completely in the same period. Hence, the efficient monetary and fiscal policy should keep into consideration before devising policies that have a greater influence on the variability of exchange rate. Keywords: Nominal Exchange Rate, Macroeconomic Variables, Terrorism, Auto Regressive Distributed Lag JEL Classifications: F02, F31, F41